Understanding gender inequity in brain health outcomes: missed stroke as a case study for intersectionality - Berkhout, Suze G.; Hashmi, Syeda; Pikula, Aleksandra (Frontiers in Global Women's Health, 2024)
Recent attention into sex and gender-based inequities surrounding outcomes for brain health disorders has generated momentum toward addressing what has been called the “brain health gap.” Importantly though, “women” are not uniform demographic group. In this perspective piece, we discuss misdiagnosis in stroke as an aspect of access and quality of care within brain health. Drawing on narrative data from a mixed methods study of young stroke survivors we suggest that while missed stroke isn't only an issue of gender, if we are going to understand gender-based gaps in access and navigation through stroke care, we have to understand how intersections of gender with age, ethnoracial identity, nationality, language, (dis)ability, and other aspects of social identity come together to create affordances as well as biases that contribute to stroke outcomes.